Pengembangan Modul Pembelajaran IPA Berbasis Contexstual Teaching and Learning Untuk Kelas IV di SD - Muthyara Daryus; Firman; Desyandri (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to describe and develop a valid and practical science learning module based on Contexstual Teaching and Learning (CTL) for grade IV at SD Negeri 22 Kuranji. The type of research used is the development (Research and Development) by using a 3-D model modification consisting of the stages of define, design, and development. This research was conducted in the even semester of the 2019/2020 school year. The questionnaire validator consisted of 1 material validator lecturer, 1 design validator lecturer and 1 language validator lecturer. Based on the results of the study, the module validation which was carried out from the aspect of science material received an assessment of 3.20, from the display aspect it obtained an assessment of 3.83 and from the aspect of language received an assessment of 4.00. Seen the average score for the assessment of the CTL-based science learning module which obtained an overall score of 3.67 with a very valid category. While the practicality test consisted of 1 teacher and 23 students. From the practicality results by the teacher, the percentage of results was 83.85% with the practical category and from the practicality by the students, the percentage of the results was 82.26% with the practical category. From the results of this study it can be concluded that the resulting CTL-based science learning module is very valid and practical to use in science learning so that it can be used in science learning in class IV SD.